PERTUMBUHAN DAN HASIL KELAPA SAWIT PADA LAHAN GAMBUT DAN PODSOLIK MERAH KUNING DI KABUPATEN SEKADAU - , ALIAS YANTO, Prof. Dr. Ir. Didik Indradewa,Dip.Agr.St. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The success of palm development is affected by climate, soil and region shape, plants sources and technical culture treatment. Recently, palm development has done in marginal land such as peat and red-yellow podsolic lands. The purpose of this research is to find out the growth and yields of palm at peat and red-yellow podsolic soil, and to find out the environmental condition of peat and red-yellow podsolic lands for palm growth. This research was conducted from March to June 2010 at 4th Division of Multi Prime Entakai Ltd., Sekumpai, and using inter-location test with randomized complete design. There were two treatments, namely, peat field and red-yellow podsolic lands with 9 replications, thus the number of sample plants were 2 x 9 x 4 = 72 plants. The result of research shows that the performance and yield of palm trees was in the similar condition with the average productivity of production age 9-13 years at the red-yellow podzolic and peat lands respectively 21.16 and 19.06 tonnes fresh fruit bunch/ha/year. Based on potential of the land suitability class including the average land suitability is 18-24 tonnes fresh fruit bunch/ha/year. The climate and land environment is categorized as the land with the limited land suitability (S3) and with the correct culture treatment of the red-yellow podzolic and peat lands have a good prospects for the palm development.